Unsupervised Clustering Analysis Based on MODS Severity Identifies Four Distinct Organ Dysfunction Patterns in Severely Injured Blunt Trauma Patients - Liu, Dongmei; Namas, Rami A.; Vodovotz, Yoram; Peitzman, Andrew B.; Simmons, Richard L.; Yuan, Hong; Mi, Qi; Billiar, Timothy R. (Frontiers in Medicine, 2020)
Background: Multiple organ dysfunction syndrome (MODS) typically peaks within 5 days post injury and is associated with a complicated clinical course; however, the type and number of distinct organ failure patterns that occur after injury are unknown. To address this, we sought to identify a MOD score parameter that highly correlates with adverse outcomes and then use this parameter to test the hypothesis that multiple severity-based MODS clusters could be identified after blunt trauma in humans. Methods: MOD score across days (D) 2-5 was subjected to Fuzzy C-means Clustering Analysis (FCM) followed by eight Clustering Validity Indices (CVI) to derive organ dysfunction patterns among 376 trauma patients that survived to discharge. Thirty-one inflammation biomarkers were assayed (by Luminex™) in serial blood samples (3 samples within the first 24 h and then daily up to day 5 post-injury) and were analyzed using Two-Way ANOVA and Dynamic Network analysis (DyNA). Results: The FCM followed by CVI suggested four distinct clusters based on MOD score magnitude between D2-5: Cluster 1 (n=199, average MOD score=0.3); Cluster 2 (n=99, average MOD score=2); Cluster 3 (n=53, average MOD score=4); and Cluster 4 (n=25, average MOD score=7). There were statistically significant differences among the four clusters regarding to in-hospital outcomes, including intensive care unit (ICU) and total hospital stay, days on mechanical ventilation, and incidence of nosocomial infection. Of the 31 biomarkers measured, IL-6, MCP-1, IL-10, IL-8, IP-10, sST2, and MIG were elevated differentially over time across the four clusters. DyNA identified remarkable differences in inflammatory network interconnectivity over time among the four clusters. Conclusion: These results suggest the existence of four distinct organ failure patterns based on MOD score magnitude in trauma patients admitted to the ICU and survive to discharge. The organ failure patterns are preceded by distinct inflammatory responses and followed by differences in in-hospital outcomes.